Powder sintering of single-phase tetrahedrite materials [Resumo] - Neves, Filipe (2020)
ABSTRACT: There is a worldwide consensus for the development and implementation of zero global-warming-potential and energy efficient technologies. This energy transition requires more progress in all aspects related with renewable technologies, including the research and innovation on new and improved materials, e.g., materials for converting thermal wasted energy into electricity.